Na+ channel regulation by Ca2+/calmodulin and Ca 2+/calmodulin-dependent protein kinase II in guinea-pig ventricular myocytes - Aiba, Takeshi (2010)
Aims Calmodulin (CaM) regulates Na+ channel gating through binding to an IQ-like motif in the C-terminus. Ca2+/CaM-dependent protein kinase II (CaMKII) regulates Ca2+ handling, and chronic overactivity of CaMKII is associated with left ventricular hypertrophy and dysfunction and lethal arrhythmias. However, the acute effects of Ca 2+/CaM and CaMKII on cardiac Na+ channels are not fully understood.Methods and results Purified NaV1.5-glutathione-S-transferase fusion peptides were phosphorylated in vitro by CaMKII predominantly on the I-II linker. Whole-cell voltage-clamp was used to measure Na+ current (INa) in isolated guinea-pig ventricular myocytes in the absence or presence of CaM or CaMKII in the pipette solution. CaMKII shifted the voltage dependence of Na+ channel availability by ≈+5 mV, hastened recovery from inactivation, decreased entry into intermediate or slow inactivation, and increased persistent (late) current, but did not change INa decay. These CaMKII-induced changes of Na+ channel gating were completely abolished by a specific CaMKII inhibitor, autocamtide-2-related inhibitory peptide (AIP). Ca2+/CaM alone reproduced the CaMKII-induced changes of INa availability and the fraction of channels undergoing slow inactivation, but did not alter recovery from inactivation or the magnitude of the late current. Furthermore, the CaM-induced changes were also completely abolished by AIP. On the other hand, cAMP-dependent protein kinase A inhibitors did not abolish the CaM/CaMKII-induced alterations of INa function.Conclusion Ca 2+/CaM and CaMKII have distinct effects on the inactivation phenotype of cardiac Na+ channels. The differences are consistent with CaM-independent effects of CaMKII on cardiac Na+ channel gating.